Logic programming with temporal constraints - Schwalb, E.; Vila, L. (Temporal Representation and Reasoning, 3rd Workshop On: Time 96, 1996)
Combines logic programming and temporal constraint processing techniques in a language called TCLP (Temporal Constraint Logic Programming), which augments logic programs with temporal constraints. Known algorithms for processing disjunctions in temporal constraint networks are applied. We identify a decidable fragment called Simple TCLP, which can be viewed as extending Datalog with limited functions to accommodate intervals of occurrence and temporal constraints between them. Some of the restrictions introduced by Simple TCLP are overcome by a syntactic structure which provides it with the benefits of reification. The latter allows quantification on temporal occurrences and relation symbols.